Optical Properties of Sb Doped Ge Films Deposited on Silicon Substrate by Molecular Beam Epitaxy - Phuong, Luong Thi Kim; Vinh, Le Thanh; Ghrib, Abdelhamid; El Kurdi, Moustafa; Boucaud, Philippe; Quynh Nga, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 34 No 3DO - 10.25073/2588-1124/vnumap.4261, 2018)
To enhance the photoluminescence effeciency of the Ge film, we can apply a tensile strain or n doping in the Ge epilayers for modifying it’s energy band gap structure. In this work, we combine both electron doping method from Sb source and inducing a tensile strain in Ge films. Sb doped Ge grown on Si(100) substrate by molecular beam epitaxy technique. The dependence of photoluminescence intensity on the substrate temperature in the range of 130-240 o C and on the Sb source temperature from 240 to 300 o C are investigated. The active electron concentration obtained up to 2.5x10 19 cm -3 . The tensile strain level in the Sb-doped Ge epilayers is twice larger than that of the P-doped Ge films using GaP solid source or PH 3 gas precursor. These results are significant in the realization of the Si based photoelectronic devices which are compatible with mainstream CMOS technology.